Medan Terjal Inklusi: Problematika Guru dalam Merancang Media Pembelajaran yang Efektif Bagi Anak Tunagrahita - Ginting, Angelina Gracia; Ulitona, Anastasia Roh; Sipayung, Dear Ezra; Simanjuntak, Ririn Ayu; Tansliova, Lili; Puteri, Anggia (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to explore the various challenges faced by teachers in designing learning media for children with intellectual disabilities, as well as to develop more targeted training policies and strategies. The method used in this study is descriptive qualitative with a focus on describing an event, behavior, problem or condition being studied. The main data collection technique in this study is interviews. The data source for this study was one of the teachers at SLB ABC Melati Aisyiyah Deli Serdang, especially as a class 5C teacher (intellectual disabilities). The findings of this study indicate that the success of implementing learning media for children with intellectual disabilities is greatly influenced by teacher readiness, limited facilities and infrastructure, variations in student characteristics, and the need for individual, interactive learning strategies supported by teacher training and adaptive evaluation